EVALUATION OF APHRODISIAC ACTIVITY AND SPERMATOGENIC EFFECT OF VIGNA MUNGO - Gupta, RB; Ahuja, A; Yadav, R.; Kabra, MP (Asian Journal of Pharmaceutical Research and Development, 2014)
According to Indian Systems of Medicine, Vigna mungo Linn, belonging to the Fabaceae family, is an important aphrodisiac (Vajikaran drug) as describe in Charak Sanhita. Vigna mungo is used for treating male sexual disorders since ancient times. In this study, the effects of alcoholic extracts of the Vigna mungo Linn. seeds on general mating behaviour, libido and potency of normal male Wister albino rats were investigated and also compared with the standard reference drug, Sildenafil citrate. Vigna mungo extract also tested for effect on spermatogenisis. Animals were divided into one control group (Group I––received saline) and two experimental groups (Groups II–III): Sildenafil citrate (4 mg/kg body weight) (Group II) and while Group III received 500 mg/kg body weight. Animals were fed PO with saline or extract or standard drug once in a day for 42 days. To analyse the mating behaviour, female rats with oestrus phase were used.The extract administered PO significantly increased the mounting frequency, intromission frequency and decreased the mounting latency, intromission latency, post ejaculatory interval and inter-intromission interval. The male reproductive organ weight increased, sperm count also increase and it is supported in histopathology slides of testies. Therefore, the results indicated that the alcoholic extracts of Vigna mungo Linn. seed produced a significant and sustained increase in the sexual activity of normal male rats at a particular dose (500 mg/kg). Therefore, the resulting aphrodisiac activity of the extract tends to support to the claim that it has traditionally been used for the treatment of sexual disorders.